A Kinetic Model for Chelating Extraction of Metals from Spent Hydrodesulphurization Catalyst by Complexing Agent - Alpaslan, Orhon; Yaraş, Ali; Arslanoglu, Hasan; Yaraş, Ali (Springer India, 2020)
In this present paper, chelating extraction of metals from spent hydrodesulphurization catalyst was carried out using ethylene diamine tetraacetic acid as complexing agent. Mo, Ni and Co metals were precipitated in ammonium molybdate, nickel dimethylglyoxime and cobalt hydroxide forms at pH:2, pH:6 and pH:10, respectively. The highest metal extraction yields (90.22% Mo, 96.71% Co, 95.31% Ni and 19.98% Al) were achieved under optimum process conditions. The activation energy values (E-a) of Co, Mo and Ni were calculated as 14.36 kJ/mol, 16.85 kJ/mol and 15.93 kJ/mol, respectively. It was determined that leaching kinetics fitted to the pseudo-first homogenous model and the chelating process was controlled by diffusion mechanism. In the light of the kinetic data, the kinetic equation including the process parameters was obtained as follows: ln(1 - x) = 1.217 x 10(-4)[C-A)(1.068) (D)(-0.929)(K/S)(-0.850) (R)(0.185) expo(-6462.6/T)]t. The results provided a new approach both for reducing the solid waste load of the petrochemical industry and for efficient recovery of metals from the spent hydrodesulphurization catalyst using EDTA.
Keywords: Chelation; Edta; Spent Hds Catalyst; Complexing Agent; Leaching; Metal Recovery